Analysis of Factors Influencing the Behavior of Mothers in Choosing Childbirth Helpers During the Covid-19 Pandemic in the Region Work of the Gunung Tua Health Center in 2021 - Povi Anggraini Harahap; Razia Begum Suroyo; Mangatas Silaen (Institute of Computer Science (IOCS), 2022)
The current situation of the Covid-19 pandemic in Indonesia has also greatly affected the access of pregnant women to health services. This study aimed to analyze the factors that influence the behavior of mothers in choosing birth attendants during the Covid-19 pandemic in the work area of the Gunung Tua Health Center in 2021. This research is a mixed method research with the Reseacrh explanatory design. The research was conducted in the working area of the Gunung Tua Health Center in October-November 2021. There were 54 samples and 15 informants, namely those who gave birth in August – Septermber 2021. Quantitative data analysis was carried out with Chi-square test and logistic regression test. While qualitative analysis is carried out with interactive analysis. The univariate analysis was that of 54 respondents, most of them were aged 36-45 years, namely 21 (38.9%) respondents, had a high school education level of 30 (55.6%) respondents, had an IRT job, which was 29 (53.7%) respondents. Bivariate results show that knowledge (p=0.040), attitude (p=0.006), trust (p=0.000), availability of access (p=0.000), family support (p=0.000), health worker information (p=0.000) affect the mother's behavior in choosing a birth aid during the Covid-19 pandemic. The most influential factor is the availability of access. Conclusion : A safe maternity place during the covid 19 pandemic is home, The maternal childbirth ratio is second and third, mothers feel worried about giving birth during the pandemic and the way for mothers to think positively is to encourage themselves, get closer to god by praying diligently. It is recommended that pregnant women can increase their knowledge in choosing childbirth helpers by actively following counseling carried out by health workers.